The role of childhood emotional maltreatment and body image dissatisfaction in problematic smartphone use among adolescents. (January 2019) - Emirtekin, Emrah; Balta, Sabah; Sural, İrfan and Kircaburun, Kagan and Griffiths, Mark D. and Billieux, Joel
Highlights: Childhood emotional maltreatment was associated with problematic smartphone use. Body image dissatisfaction was associated with problematic smartphone use. Depression and social anxiety were associated with problematic smartphone use. There were partial mediating effects of mediator variables in the model. Problematic smartphone use could be considered in clinical practice. Abstract: Growing empirical evidence has identified specific psychological and contextual risk factors associated with problematic smartphone use (PSU). However, the potential direct and indirect impact of childhood emotional maltreatment (CEM) on PSU remains largely unexplored, despite the established role of CEM in the onset of other excessive, problematic, and addictive behaviors. Consequently, the purpose of the present study was to test the direct and indirect relationships of emotional abuse and neglect (two facets of CEM) with PSU via specific mediational pathways including body image dissatisfaction (BID), social anxiety, and depression. The sample comprised 443 adolescents who completed a questionnaire that included assessment tools of aforementioned variables. Multiple mediation model results indicated that CEM was directly and indirectly associated with PSU via BID, depression, BID-related depression, and BID-related social anxiety. Results suggested that emotionally traumatic experiences were associated with PSU in adolescents and that this relationship may partially be explained by BID and psychosocial risk factors. The present study draws caution to the amplifying roles of CEM and BID on increased PSU. The results of the study have important clinical and public health implications, but additional research is needed before interventions can be developed and implemented on the basis of present results.